The Importance of Gut Microbiota on Choline Metabolism in Neurodegenerative Diseases - Majid Eslami; Farnaz Alibabaei; Ali Babaeizad; Seyedeh Zahra Banihashemian; Mahdi Mazandarani; Aref Hoseini; Mohammad Ramezankhah; Valentyn Oksenych; Bahman Yousefi (Biomolecules)
The gut microbiota is a complex ecosystem that influences digestion, immune response, metabolism, and has been linked to health and well-being. Choline is essential for neurotransmitters, lipid transport, cell-membrane signaling, methyl-group metabolism and is believed to have neuroprotective properties. It is found in two forms, water-soluble and lipid-soluble, and its metabolism is different. Long-term choline deficiency is associated with many diseases, and supplements are prescribed for improved health. Choline supplements can improve cognitive function in adults but not significantly. Choline is a precursor of phospholipids and an acetylcholine neurotransmitter precursor and can be generated de novo from phosphatidylcholine via phosphatidylethanolamine-N-methyltransferase and choline oxidase. Choline supplementation has been found to have a beneficial effect on patients with neurodegenerative diseases, such as Alzheimer’s disease (AD), by increasing amyloid-β, thioflavin S, and tau hyper-phosphorylation. Choline supplementation has been shown to reduce amyloid-plaque load and develop spatial memory in an APP/PS1 mice model of AD. Choline is necessary for normative and improved function of brain pathways and can reduce amyloid-β deposition and microgliosis. Clinical research suggests that early neurodegenerative diseases (NDs) can benefit from a combination of choline supplements and the drugs currently used to treat NDs in order to improve memory performance and synaptic functioning.